Current condition of shallow-water benthic foraminifera in Manado bay, Indonesia - Mamuaja, Jane M.; Mandagi, Stephanus V.; Lasut, Markus T. (AQUATIC SCIENCE & MANAGEMENT, 2023)
Coral reef community in Manado Bay is under pressure due to human activities in areas in and around Manado. In order to be able to wisely manage the bay area and the coral reefs in it, information about present conditions is needed. The use of marine organisms as bioindicators is one way to find information about the condition, and organisms such as foraminifera have the potential to be used as some species share the same requirement for water quality as the corals. Sampling for the foraminifera was carried out at 10 locations, and the depth of water ranged from 2.5 m to 7.0 m. The samples obtained were washed through a 63 μm sieve and dried. The separation of foraminifera tests from other sediments was done under a stereomicroscope and they were then identified to genus level. A total of 40 genera was identified among 3194 specimens. To get the FoRAM Index value, the foraminifera was categorized into three functional groups. 8 genera were categorized as symbiont-bearing group, 8 as opportunistic group, and 29 as heterotrophic group. FoRAM Index was found to be varied from 2.06 to 9.19 which indicated that Manado Bay water condition is also varied among the sampling area. In general based on the data obtained, it is assumed that water in Manado Bay is conducive for coral reef growth.